Asian Rhinoplasty: Preoperative Simulation and Planning Using Adobe Photoshop - Kiranantawat, Kidakorn (Semin Plast Surg, 2015)
A rhinoplasty in Asians differs from a rhinoplasty performed in patients of other ethnicities. Surgeons should understand the concept of Asian beauty, the nasal anatomy of Asians, and common problems encountered while operating on the Asian nose. With this understanding, surgeons can set appropriate goals, choose proper operative procedures, and provide an outcome that satisfies patients. In this article the authors define the concept of an Asian rhinoplasty—a paradigm shift from the traditional on-top augmentation rhinoplasty to a structurally integrated augmentation rhinoplasty—and provide a step-by-step procedure for the use of Adobe Photoshop as a preoperative program to simulate the expected surgical outcome for patients and to develop a preoperative plan for surgeons.